Efeito dos métodos analítico e situacional sobre o desempenho tático-técnico, a tomada de decisão e a carga interna do treinamento em atletas de voleibol de praia - Grisi, Raianne de Brito (2019)
One way to improve the performance of the teams is to plan and organize training in order to maximize gains and minimize the time spent, by using teaching methods. In addition, training monitoring and decision making (DM) are factors that influence performance. DM is considered a factor of cognitive ability and influences tactical performance in athletes, on the other hand, the monitoring of training is essential to direct the training load for each phase of the training. The objective of the study was to analyze and compare the tactical-technical performance, the TD of the attack and the internal training load in the analytical and situational training methods in beach volleyball athletes. We selected 16 male athletes from the U-15 (n=6) and U-17 (n=10) categories, divided randomly into two groups according to teaching methods: analytical (n=8) and situational (n=8). In addition, two U-19 athletes were recruited to form a special double. The study lasted 10 weeks and was divided into three main phases: pre-intervention evaluations, intervention (6 weeks) and post-intervention. In the pre-intervention phase, the evaluations of the tactical-technical performance of the complex 1 (service reception, set and attack) and DM of the attack were performed. In the intervention phase, the subjective perception of the effort and the duration of the training during a microcycle (three sessions) were evaluated. And in the post-intervention phase it was performed the tactical-technical performance of the complex 1 and DM of the attack. The results showed that in the reception efficiency there was a time interaction between the methods (F (1.22) = 3.435; p = 0.077; ƞ 2 = 1.24 high) and in the pre vs. powders of the situational method (F = (1,22) = 7,145; p = 0,014), in the effectiveness of the time interaction between the methods (F (1,22) = 8,345; p = 0,009; ƞ 2 = 1,28 high) and pre vs. powders of the situational method (F = (1.22) = 1.039; p = 0.004). In the reception coefficient, there was a time interaction between the methods (F (1.22) = 3.885; p = 0.061; ƞ 2 = 1.1 high) and in the pre vs. powders of the situational method (F = (1,22) = 5,829; p = 0,025), in the survey coefficient, there was a time interaction between the methods (F (1,22) = 5,78; p = 0,025; ƞ 2 = -56.86 low) and pre vs. powders of the situational method (F = (1.22) = 6.27; p = 0.02). In the decision making of the attack the situational method showed a significant effect on the interaction time (pre x post) (F (1,22) = 6,421; p = 0,019; ƞ 2 = 0,55 moderate). At CIT, she observed a significant reduction in the 3rd session compared to the 2nd (p = 0.006; delta% = -195.71; TE = high). In article 1 it can be concluded that the situational method, when compared to the analytical method, was more effective for the tactical-technical training in the reception and set of beach volleyball athletes. In article 2 it can be concluded that the internal training load evaluated in three sessions of experimental protocol with young beach volleyball athletes does not differ between analytical and situational teaching methods.